2021
DOI: 10.3389/fcell.2021.649875
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Interacting Antifungal Peptides

Abstract: The incidence of invasive fungal infections is increasing worldwide, resulting in more than 1.6 million deaths every year. Due to growing antifungal drug resistance and the limited number of currently used antimycotics, there is a clear need for novel antifungal strategies. In this context, great potential is attributed to antimicrobial peptides (AMPs) that are part of the innate immune system of organisms. These peptides are known for their broad-spectrum activity that can be directed toward bacteria, fungi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 254 publications
(300 reference statements)
0
62
0
1
Order By: Relevance
“…Some studies have found that the intracellular targets can be affected by AMPs though ROS production, programmed cell death, mitochondrial dysfunction, disruption of cation homeostasis, ATP efflux, cell cycle impairment, autophagy, and vacuolar dysfunction. AMPs, which finish interacting with the target, can be internalized or can remain outside the fungal cell ( 35 ).…”
Section: Biological Function and Active Mechanism Of Ampsmentioning
confidence: 99%
“…Some studies have found that the intracellular targets can be affected by AMPs though ROS production, programmed cell death, mitochondrial dysfunction, disruption of cation homeostasis, ATP efflux, cell cycle impairment, autophagy, and vacuolar dysfunction. AMPs, which finish interacting with the target, can be internalized or can remain outside the fungal cell ( 35 ).…”
Section: Biological Function and Active Mechanism Of Ampsmentioning
confidence: 99%
“…Pathogenic fungi are considered a greater threat to plant and animal biodiversity than other taxonomic classes [ 101 ]. As part of the intrinsic immune system, BAMPs have great potential to be developed as novel antifungal agents due to their broad-spectrum activity, selective targeting, multiple mechanisms of action, and limited cell cytotoxicity [ 7 , 102 ]. Elucidating the functional mechanism of BAMPs is key to uncovering their application potential and developing new therapeutic approaches.…”
Section: Antimicrobial Activity Of Bamps Against Targeted Organisms and Cancer Cellsmentioning
confidence: 99%
“…Unlike the well-known PTI (pattern-associated triggered immunity) and ETI (effector-associated triggered immunity) immune responses in plants, the broad-spectrum antimicrobial activity of BAMPs is largely due to targeting lipid structures of microbial cell membranes, thus disrupting membrane structure [ 3 , 4 ] and leading to content leakage and cell death through a combination of membrane lysis and cytotoxicity [ 5 , 6 ]. However, more complex mechanisms also exist, including interaction with specific lipids, cell cycle arrest, reactive oxygen species (ROS) production, programmed cell death, autophagy, cell signaling, and immune response [ 7 , 8 ]. BAMPs are thus responsible for durable resistance in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Sporothrix globosa is the predominant etiologic agent that brings about sporotrichosis in East Asia, notably in northeast China ( Yao et al, 2020 ). An epidemiologic study found that approximately 1.6 million people die from fungal infections in the world each year ( Struyfs et al, 2021a ), and a global increase in sporotrichosis incidence occurs every year, especially in the tropical and subtropical regions ( Chakrabarti et al, 2015 ). Current therapies to treat sporotrichosis are very limited, which mainly include antifungal drugs, photodynamic therapy, thermotherapy, cryotherapy, and surgery, and the effects are still far from satisfactory ( Honse et al, 2010 ; MF Matos et al, 2020 ; Soeiro Sampaio et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The plasma membrane disruption pathway indicates that the positively charged antimicrobial peptides bind to the negatively charged membrane of the pathogens, destroying its integrity, leaking contents, and causing death ( Guilhelmelli et al, 2013 ; Deslouches and Di, 2017 ; Mwangi et al, 2019 ). In addition, non-membranolytic cytotoxicity is also involved in antimicrobial activity, such as genetic material damage, immune regulation, and apoptosis ( Wassing et al, 2015 ; Struyfs et al, 2021b ). Unlike traditional antibiotics, antimicrobial peptides have many advantages such as quick killing effect and low tendency to induce resistance ( Guilhelmelli et al, 2016 ; Xu et al, 2020 ; Jayawant et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%